Career trajectories of Chinese self-initiated early career expatriates in Hungary: Two-step migration pathway perspective? - Li, Xueyan; Primecz, Henriett (Vezetéstudomány / Budapest Management Review, 2025)
This paper explores the career trajectories of Chinese self-initiated expatriates who relocated to Hungary to study and evaluates their career prospects abroad. By examining the two-step migration pathway, this paper uncovers the relative merits of three potential career choices, namely whether to return, remain in Hungary, or move to another European country. This research employs a constructivist grounded theory approach with semi-structured interviews with 22 Chinese graduates. Additional qualitative data, including observations, textual analyses of publicly available testimonies, and a research diary, complement the study. The findings reveal ambiguity in the advantages and disadvantages of each potential choice. The empirical material suggests that women face even greater challenges in this regard, as they experience considerable pressure to start a family, preferably in China. As a result, their self-initiated expatriation intentions are often played down. The study also highlights the difficulties of transferring social, cultural, and career capital into a new environment.